2020
DOI: 10.1002/cmdc.202000269
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Luminescent LnIII Fluoride Core–Shell Nanoparticles with Acetylsalicylic acid (Aspirin): Synthesis, Spectroscopic and in Vitro Hemocompatibility Studies

Abstract: Luminescent lanthanide fluoride core–shell (LaF3:Tb3+,Ce3+@SiO2‐NH2) nanoparticles, with acetylsalicylic acid (aspirin) coated on the surface have been obtained. The synthesized products, which combine the potential located in the silica shell with the luminescent activity of the core, were characterized in detail with the use of luminescence spectroscopy, Fourier transform infrared spectroscopy (FTIR), X‐ray diffraction (XRD), and transmission electron microscopy (TEM) methods. The in vitro effects of the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…The broad emission peak at 414 nm belong to the n!π* transitions of the aspirin molecule. [38,42] The weak emission of Eu 3 + is because of the very weak energy transfer from the ligand to the Eu 3 + ion due to the lesser overlap between Eu 3 + absorption and aspirin emission (Figure 2d). In the case of 1,2,4,5-BTCA-capped LaF 3 :Eu 3 + NPs, the emission spectrum is similar to IA-capped LaF 3 :Eu 3 + NPs, only in the excitation spectra the peak maxima's are observed at 259 nm (high intensity) and 293 nm (low intensity; Figure 2e).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The broad emission peak at 414 nm belong to the n!π* transitions of the aspirin molecule. [38,42] The weak emission of Eu 3 + is because of the very weak energy transfer from the ligand to the Eu 3 + ion due to the lesser overlap between Eu 3 + absorption and aspirin emission (Figure 2d). In the case of 1,2,4,5-BTCA-capped LaF 3 :Eu 3 + NPs, the emission spectrum is similar to IA-capped LaF 3 :Eu 3 + NPs, only in the excitation spectra the peak maxima's are observed at 259 nm (high intensity) and 293 nm (low intensity; Figure 2e).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of the standard haemocompatibility assays, it can be concluded that all tested nanoparticles: 1) are nonhaemolytic, namely, no increase in the RBC membrane permeability was observed after both short and long-time incubation, 2) do not alter the discoid shape of RBC (in vitro results mean that they will not adversely affect the rheological properties of RBC and the viscosity of blood in vivo), 3) do not significantly affect the RBC sedimentation rate, 4) compound 6 interacts with the RBC membrane without inducing alteration in the molecular membrane structure, 5) ligand-sensitised LaF 3 :Eu 3 + and SrF 2 :Eu 3 + nanoparticles seem to have similar properties to the previously studied LaF 3 :Tb 3 + , Ce 3 + , @SiO 2 -NH 2 nanoparticles. [38] These findings may be useful in the process of creating new nanoparticles that are nontoxic in vitro for living cells and subsequent research on the delivery of biomolecules, for example, to their target tissues or organs. Our observations proved that the tested nanomaterials are highly biocompatible compounds in vitro and can be further investigated for biomedical application in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations